Impact of Intraoperative Magnetic Resonance Imaging and Other Factors on Surgical Outcomes for Newly Diagnosed Grade II Astrocytomas and Oligodendrogliomas: A Multicenter Study. Issue 1 (27th July 2020) - Yahanda, Alexander T; Patel, Bhuvic; Shah, Amar S; Cahill, Daniel P; Sutherland, Garnette; Honeycutt, John; Jensen, Randy L; Rich, Keith M; Dowling, Joshua L; Limbrick, David D; Dacey, Ralph G; Kim, Albert H; et al.
Abstract: BACKGROUND: Few studies use large, multi-institutional patient cohorts to examine the role of intraoperative magnetic resonance imaging (iMRI) in the resection of grade II gliomas. OBJECTIVE: To assess the impact of iMRI and other factors on overall survival (OS) and progression-free survival (PFS) for newly diagnosed grade II astrocytomas and oligodendrogliomas. METHODS: Retrospective analyses of a multicenter database assessed the impact of patient-, treatment-, and tumor-related factors on OS and PFS. RESULTS: A total of 232 resections (112 astrocytomas and 120 oligodendrogliomas) were analyzed. Oligodendrogliomas had longer OS ( P  < .001) and PFS ( P  = .01) than astrocytomas. Multivariate analyses demonstrated improved OS for gross total resection (GTR) vs subtotal resection (STR; P  = .006, hazard ratio [HR]: .23) and near total resection (NTR; P  = .02, HR: .64). GTR vs STR ( P  = .02, HR: .54), GTR vs NTR ( P  = .04, HR: .49), and iMRI use ( P  = .02, HR: .54) were associated with longer PFS. Frontal ( P  = .048, HR: 2.11) and occipital/parietal ( P  = .003, HR: 3.59) locations were associated with shorter PFS (vs temporal). Kaplan-Meier analyses showed longer OS with increasing extent of surgical resection (EOR) ( P  = .03) and 1p/19q gene deletions ( P  = .02). PFS improved with increasing EOR ( P  = .01), GTR vs NTR ( P  = .02), and resections above STR ( P  = .04). Factors influencing adjuvant treatment (35.3% of patients) included age ( P  = .002, odds ratio [OR]: 1.04) and EOR ( P  = .003, OR: .39) but not glioma subtype or location. Additional tumor resection after iMRI was performed in 105/159 (66%) iMRI cases, yielding GTR in 54.5% of these instances. CONCLUSION: EOR is a major determinant of OS and PFS for patients with grade II astrocytomas and oligodendrogliomas. Intraoperative MRI may improve EOR and was associated with increased PFS.